1996
DOI: 10.1007/bf00417902
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained dysphagia: Viscous swallow-induced esophageal dysmotility

Abstract: Dysphagia is a manifestation of several clinical conditions of diverse origin. In spite of the variation in these disease entities in terms of their etiology, clinical presentation, natural history, and treatment, the mechanism of this clinical complaint is not always clear. We studied a group of patients with dysphagia for solids in whom no anatomic or motor abnormalities were encountered on standard studies. The group consisted of 37 patients, 25 women and 12 men, who were complaining of dysphagia of 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…NOD patients exhibited more oesophageal dysmotility than healthy controls. In addition, our data re‐confirmed the previous observation in NOD patients that the symptom of dysphagia can be provoked during standard manometry with swallowing 10,17 . Therefore, our study would suggest that oesophageal dysmotility may play a limited role in the symptomatic generation of dysphagia during swallowing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…NOD patients exhibited more oesophageal dysmotility than healthy controls. In addition, our data re‐confirmed the previous observation in NOD patients that the symptom of dysphagia can be provoked during standard manometry with swallowing 10,17 . Therefore, our study would suggest that oesophageal dysmotility may play a limited role in the symptomatic generation of dysphagia during swallowing.…”
Section: Discussionsupporting
confidence: 89%
“…This study clearly showed that viscous swallows not only provoked symptoms in most swallows, but also produced impaired bolus transit in a majority of swallows, although there was no significant difference regarding oesophageal manometry when comparing liquid with viscous swallows. The current findings are similar to a recent study with solid swallowing, 10 but are different to the results of a previous investigation, which has demonstrated a significant difference between the response rate of dysphagia provoked by viscous (89%) and liquid swallows (9%) 17 . This discrepancy may possibly be explained by different inclusion criteria of patients’ enrolment because that study included the subjects only with normal standard oesophageal manometry.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…With regards to diagnosis, most patients do not experience oesophageal symptoms with single swallows of water, but rather during and after a meal; however, interpreting this complex data is difficult with conventional manometry 85 86. As shown in some of the clinical cases, HRM makes it possible to extract meaningful information from physiological challenges (e.g.…”
Section: Future Directions Of Oesophageal Hrmmentioning
confidence: 99%
“…Results from the mixed model ANOVA revealed that tegaserod had no effect on median LOS pressure compared with placebo [23 (18-29) vs. 23 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) …”
Section: Effect Of Tegaserod On Oesophageal Peristalsis and Sphinctermentioning
confidence: 99%